Program Kesejahteraan Sosial Melalui Santunan Pendidikan untuk Anak Yatim Piatu dan Fakir Miskin di SMK JAPA Pati - Hamidulloh Ibda (Jurnal Penelitian Kesejahteraan Sosial, 2019)
This research aims at finding out social welfare programs for orphaned students and the needy through educational compensation. The location of the study was chosen at Jamaah Pasrah (JAPA) Vocational High School in Dukuhseti Village, Dukuhseti Subdistrict, Pati District, Central Java. The reason for choosing this school because it implemented an education compensation program for orphans and the needy from entering in school until graduating. Data collection of this study uses interview, observation, and document review techniques. Data and information collected, then analyzed qualitatively and described using narrative. The results of the study show that the social welfare program through education compensation is able to improve the social welfare of orphans through productive assistance to the orphans and the needy students covering all fees from admission to graduation. All models of education provision for orphans are free, while the needy are only free from the cost of donating education and students unless they ask for relief. The education compensation of JAPA Vocational High School Pati is able to improve social welfare in the aspect of education. This education compensation reduces the number of school dropouts in a year of at least 10-15 orphans and the needy. In 2017, the JAPA Vocational High School gave educational assistance to 8 orphaned and 12 needy students. While in 2018, providing education compentation to 17 orphan students.Â Keywords: Social Welfare; Educational Compensation; Orphans and The Needy